Islam, Radikalisme dan Terorisme - Nafilah, Ainun; Arnelsyah, Faridz; Ardiyanti, Shaiyla Nova; Irmansyah, Muhammad (Jurnal Penelitian Multidisiplin Ilmu, 2025)
This study aims to analyze the phenomenon of radicalization and terrorism through interpretation with the maudhu’i method and a review of related hadiths and the opinions of scholars. The results of the discussion of this study are the roots of radicalization and terrorism, the history of the birth of radicalism and terrorism and the causes of radicalism and terrorism. Radicalism is the root of terrorism that arises due to a narrow understanding of religion and intolerance. Factors such as political pressure, religious sentiment, and mass media contribute to the development of radicalism. History shows that radicalism has existed since the time of the Prophet Muhammad SAW and is often related to politics. Islam rejects extremism and teaches fair conflict resolution, and emphasizes that true jihad is building a peaceful society. Therefore, a comprehensive understanding of religious teachings is very important to avoid extreme thinking that damages the image of Islam.